DIVERSITY OF ENDOPHYTIC FUNGI ASSOCIATED WITH FRUITS AND LEAVES OF TAMARIND (Tamarindusindica L.) BASED O N ITS RIBOSOMAL DNA SEQUENCES - Nur Ain Izzati Mohd Zainudin; Nurul Asyiqin Mohd Zaini; Nurul Huwaidah Md Nizam; Dayang Fatin Zafira Awg Zainal Abidin; Nor Izanis Azni Mohd Nazri (SEAMEO BIOTROP, 2021)
Plant-associated microbes are among the important natural resources that abundantly exist in natural environment such as endophytic fungi. The studies on endophytic fungi in medicinal plants have allowed the discovery of numerous fungi species and their hidden potentials. Therefore, this study focused on the isolation and identification of endophytic fungi from several plant parts of tamarind such as leaves and fruits. A total of 69 fungal cultures were successfully isolated and identified into 33 distinct species from 14 genera based on morphological characteristics and internal transcribed spacer (ITS) sequence analysis using a Maximum Likelihood method. There were six different species obtained from the genus Colletotrichum (C. aenigma, C. brevisporum, C. cobbittiense, C. fructicola, C. gloeosporioides and C. siamense), and Diaporthe (D. arecae, D. ceratozamiae, D. phaseolorum, D. pseudomangiferae, D. pseudooculiÂ and D. pseudophoenicicola), four species of Aspergillus (A. aculeatus, A. carbonarius, A. flavus and A. tubingensis), three species of Curvularia (C. aeria , C. geniculata and C. lunata) and Nigrospora (N. lacticolonia, N. oryzae and N. sphaerica), two species of Lasiodiplodia (L. pseudotheobromae and L. theobromae) and Penicillium (P. rolfsii and P. verruculosum). Other fungal species that were also identified are Botryosphaeria mamane, Fusarium solani, Perenniporia tephropora, Phyllosticta fallopiae, Sarcostroma bisetulatum, Trichoderma asperellum and Xylaria feejeensis. The isolates were grouped into different clades according to their class. In conclusion, endophytic fungi isolated from tamarind plant are diverse and provides an insight into species diversity of endophytic fungi in tamarind.